Use of Generative Artificial Intelligence in High School: A Systematic Review (2020–2025) (Praxis Educativa, 2026)
The rapid expansion of Generative Artificial Intelligence (GAI) has transformed various fields, including education. This systematic review analyzed eighteen empirical studies from the past five years on the use of GAI among high school students. The research followed the PRISMA methodology, and data were collected from databases such as Education Source, Academic Search Ultimate, ERIC, and Scopus. The results revealed that students use GAI for  sundry purposes: learning support, task automation, idea generation, and problem-solving. The review also highlights the tension between the instrumental use of these tools and the ethical dilemmas they raise, such as plagiarism and academic dishonesty, which can compromise authentic learning. The study concludes by emphasizing the need for further research in k-12 education.